Shear-free perfect fluid theorems in general relativity - Sikhonde, Muzikayise Edward (Department of Mathematics and Applied Mathematics, 2023)
We present a detailed method for proving shear-free perfect fluid theorems in General Relativity. This method uses the (1+3)-covariant formalism to establish the consistency of the Einstein gravitational field equations under the barotropic shear-free perfect fluid condition. Using a Mathematica package xTensor, we were able to prove the following cases: the case where the pressure is constant, the acceleration vector is parallel to the vorticity, the components of a rescaled acceleration vector field orthogonal to the vorticity are basic and the case where the dot product of the rescaled acceleration vector field and the unit vorticity vector is basic, leading to the existence of a Killing vector along the vorticity